Gambaran Pemberian Terapi Senam Kaki Diabetes pada Lansia dengan Diabetes Mellitus Tipe II - I Made Candra Dinata; Komang Ayu Henny Achjar; I Ketut Gama; Ketut Sudiantara (Jurnal Gema Keperawatan, 2022)
Diabetes melitus type II occurred because due to the introduction of resistance which the cells in the body insulin that are unable to respond to fully insulin or caused by the increase in blood sugar because decreased secretion of insulin that are low by the glands of the pancreas. Diabetic foot exercises therapy is the treatment of diabetes melitus in non pharmacology, this therapy done 3 times a week for 30-40 minutes to help launch circulatory on the foot , control blood glucose , strengthen the legs and prevent deformities feet. This study aims to determine the description of giving diabetic foot exercises therapy for elderly with diabetes melitus type II. This research uses descriptive research.The population as many as 50 elderly people with diabetes melitus type ii with samples from 47 respondents. The result of this research shown majority of respondents aged 60-69 year as 55,3 %, majority women as much as 76,6 %, The average blood glucose levels before it was given diabetic foot exercises therapy is 204,74 mg/dL and after these gymnastic feet diabetes is 189,55 mg/dL. Overall, respondents are able to by to do therapy gymnastic feet diabetes properly a number of 93,6 % . Based on the result of this research it can be concluded that gymnastic feet diabetes therapy can be decrease blood glucose when blood glucose levels and researchers hope that large gymnastic feet diabetes therapy to continue as physical exercise to control blood glucose levels.